When Local Bone Pain Is Just the Tip of the Iceberg-A Case Report of Three Patients With Chronic Multifocal Recurrent Osteomyelitis and Some Red Flags to Help Make the Diagnosis - Holly Wobma; Diego Jaramillo; Lisa Imundo (Frontiers Media S.A., 2019)
Chronic recurrent multifocal osteomyelitis (CRMO) is an uncommon cause of chronic inflammatory bone pain in children that can be disabling. Often, this diagnosis is considered only after a prolonged workup, leading to frustration for families and unnecessary interventions for patients. Here we describe three cases of CRMO to increase awareness of how it may present. The first patient had a typical presentation of focal bone pain (knee), for which she underwent bone scan (hint of >1 lesion), had a bone biopsy to rule out malignancy, received empiric antibiotics for presumed infection, and finally had whole-body imaging confirming CRMO when symptoms persisted. The second patient had a similar workup, but initially presented with clavicular pain. This location should raise suspicion for CRMO, as it is an uncommon location for infectious osteomyelitis. The third patient presented with delayed growth and right hip pain, and simultaneously developed palmoplantar pustulosis. These secondary findings can also serve as red flags for CRMO, as it has been linked to this skin condition and inflammatory bowel disease. All patients improved on non-steroidal anti-inflammatory (NSAID) medications, methotrexate, and/or tumor necrosis factor (TNF)-α antagonists. By raising awareness of clinical findings suggestive of CRMO, this report may help expedite diagnosis, so patients can be started on anti-inflammatory therapy.